Green Behaviour of Tourists in the Cultural Heritage Destination of Borobudur Temple - Prinanda, Nathaniel Aji; Tirtawati, Ni Made; Mertha, I Wayan (Politeknik Negeri Bali, 2025)
Tourism is one of the economic sectors that has a major impact on ecosystems, so its sustainability is receiving increasing attention in academic literature. The sustainability approach cannot be seen from the destination as the supply side only, but also from the demand side, namely tourists. However, limited research has examined the behavioral side of tourists, particularly the factors driving green behavior in cultural heritage destinations leaving a critical gap in understanding demand-side sustainability. As a UNESCO World Heritage site, Borobudur Temple faces challenges in maintaining sustainability amid high tourist activity. Although conservation efforts have been implemented, the extent and drivers of tourists’ green behavior remain unclear. This study employs a quantitative design using a structured questionnaire distributed to 160 purposively selected domestic tourists at Borobudur Temple. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) with SmartPLS to identify the influence of internal and external factors on green behavior. The findings reveal that environmental aspects dominate tourist green behavior, followed by social and economic aspects. Internal factors, particularly trusted values, show a slightly stronger influence than external factors, although aesthetic experience also plays a key role. Conversely, destination knowledge and habitual green actions were found to be weak points. These results highlight the need for sustainability strategies that combine value-based education, improved informational tools, and behavioral nudges to help translate environmental awareness into consistent tourist actions.